Bubbles in Insulating Liquids: A Short Review - Danikas, M. (Engineering, Technology & Applied Science Research, 2019)
This paper deals with the influence of bubbles in insulating liquids and their role in liquid breakdown. Bubbles play a deleterious role in the dielectric strength of insulating liquids. Depending on their shape and localized electric field, bubbles may significantly lower the dielectric strength of insulating liquids. The present paper offers a short review – albeit incomplete – on the role of bubbles and tries to elucidate their relation to the total breakdown of dielectric liquids. It also proposes some further fields of research.